The Concept Of Muraqabah From Hadith Perspective And Its Understanding Among Marriage Consultation Officer - Nurul Hanis Sufia Bt Othman; Noornajihan Ja‘afar (USIM Press, 2024)
Journal of Hadith Studies Volume 8 Page (23-33)